2010
DOI: 10.1016/j.contraception.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Antimullerian hormone and obesity: insights in oral contraceptive users

Abstract: Background The study was conducted to examine the impact of oral contraceptives (OCs) on serum antimullerian hormone (AMH) levels by obesity status in reproductive-age women. Study design Ovulatory women, ages 18–35 years, of normal (< 25 kg/m2; n = 10) and obese (> 30 kg/m2; n = 10) body mass index (BMI) received a low-dose OC (20 mcg ethinyl estradiol/100 mcg levonorgestrel) for two cycles. Serum samples obtained at several time points during active pill use and hormone-free intervals were analyzed for AMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
73
5
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 19 publications
13
73
5
4
Order By: Relevance
“…In this respect, various results have been reported regarding the impact of steroid suppression on serum AMH levels. Some studies reported null effect of OCP treatment on serum AMH levels [18,21,22], whereas others revealed suppressed AMH levels in normal cycling women pretreated with OCP [1,15]. In a recent case report it was demonstrated that during 16 week course of menotropin treatment both serum AMH and AFC increased in an IHH patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, various results have been reported regarding the impact of steroid suppression on serum AMH levels. Some studies reported null effect of OCP treatment on serum AMH levels [18,21,22], whereas others revealed suppressed AMH levels in normal cycling women pretreated with OCP [1,15]. In a recent case report it was demonstrated that during 16 week course of menotropin treatment both serum AMH and AFC increased in an IHH patient.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have evaluated the association between AMH and BMI [11,[14][15][16][17][18][19][20][27][28][29][30][31]. (Table 4) These study results can be classified under two groups: (1) studies which suggest presence of a negative correlation between AMH levels and BMI, (2) studies which suggest that there is no correlation between BMI and AMH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because recent findings suggested an influence of OC-use on AMH levels, we adjusted for OC-use in model 1 (23). In the second model, we additionally corrected for FM (kg) (model 2) because obesity has been previously related to serum AMH levels (24). Thirdly, we added age at menarche to the model (model 3), and finally SES was added (model 4).…”
Section: Discussionmentioning
confidence: 99%